IMPLEMENTASI UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG PENERAPAN HELM BERSTANDAR SNI DI KOTA SEMARANG - Rini Septiani; Margaretha Suryaningsih; Dyah Lituhayu (Journal of Public Policy and Management Review, 2013)
Purpose of this study ato determine whether there is communication or relationship between the government and the public on the implementing of law number 22 of 2009 on the application of SNI helmet standards in the city of Semarang. Used theory is the theory of Merilee S. Grindle, the study was designed and analyzed qualitatively deksriptif. Data collection was done by library research, observation, and in-depth interviews with a number of informants. Analysis used is deductive analysis, because the analysis of the data ini the study of the standard helmet SNI is taken based on the phenomenon that is being seen.The result of this study indicate a lack of socialization is intensified by Satlantas Polrestabes to the community in the implementing of Semarang city law number 22 of 2009 on the application of ISO-Standards helmets in the city of Semarang. Implementing of the application program needs to aa a more effective from of activity in the socialization process. So that people can understand the purpose of the policy, and shape its program of activities must be done continuously.It can be concluded that the standard helmet SNI policy implementing in the city of Semarang was considered quite good. But to get maximum result in its implementing, should be stepped up Satlantas Polrestabes continous dissemination to all the people in the city of Semarang.